Changes in Trunk Muscle Activity when Holding an Object in Place ―Focusing on the Distance Between Object and Body― (International Journal of Physiotherapy, 2024)
Background: Sports events that involve heavy lifting include weightlifting and judo. Low back pain has been reported not only in these sports activities but also in jobs that require heavy weightlifting. This study focused on the posture used when holding an object in place since posture forms the basis of motion when lifting or carrying an object. The purpose of the study was to clarify the changes in muscle activity of the trunk based on the distance between the object and the body by surface electromyography (EMG).Methods: EMG of the trunk muscles was measured in a resting standing position in which the subjects felt comfortable and in a standing position while holding an object. Dumbbells of two weights, 5 kg and 10 kg, were used as the weighted objects. The distances between the dumbbell and the body were set at 10 cm, 20 cm, and 30 cm, and the EMG of the trunk muscles was recorded. The relative values of integrated electromyography and the median power frequency were calculated.Results: The results of this study indicate that control by the sacrospinal complex increases with the distance between the body and the object (p < 0.01).Conclusion: This suggests that the level of activity required of the rectus abdominis remains the same at rest as when holding the object and that the activity of the sacrospinal complex should be adjusted considering the distance between the object and the body.